Assessment of heavy metals and thermal properties of soil‐rice‐husk system collected from three districts of Bangladesh (Dhaka University Journal of Biological Sciences, 2018)
This study was conducted to evaluate the contamination of heavy metals and their thermogravimetric properties in the soil-rice-husk system. Heavy metals concentration was determined by Atomic Absorption Spectroscopy (AAS) and thermal property was also analyzed by using Thermo Gravimetric Analyzer (TGA). Metals uptake in rice crop grown in soils of three different areas (Savar, Chapainawabganj and Gazipur) in Bangladesh was studied. Soil, rice husk and rice samples were analyzed after microwave acid digestion. Heavy metals concentration detected in rice samples decreases in the following order as Fe > Mn > Zn > Cu > Ni > Co > Cd > Pb. The metal content in husk was higher than in corresponding rice. Fe concentration was higher than other metals in soil, husk and grain samples. The concentrations of Cd and Pb in the soil were found to be below the detection limit and the order of the other heavy metals as Fe > Mn > Zn > Cu > Ni. The thermal properties of the soil-ricehusk system did not show any significant visible variation during this experiment except for the soil of the Gazipur areas. The residual mass obtained from the TG thermogram helps to make a relation between the quality of soil and the rate of uptake of heavy metals by rice or its husk.Dhaka Univ. J. Biol. Sci. 27(2): 163-173, 2018 (July)